Blockchain Technology Application for Information System Security in Education - Ajeng, Michiko; Kirei, Anaya; Amanda, Keiko (IAIC Bangun Bangsa, 2023)
The benefit of using blockchain technology for information system security in the field of education is that all entered data cannot be easily faked, lost, or damaged. With blockchain, one can also communicate data and information instantly and be decentralized without depending on third parties. Blockchain is a distributed ledger that effectively and efficiently records transactions between two parties in a verifiable and everlasting way. Yet, even though blockchain technology has not yet been applied extensively in the field of education Yet, to meet the goals of this study and produce results that apply to the field of education, researchers attempt to assess the security of information systems in education using fingerprints by integrating cryptographic hash security sensors. These topics and the SWOT analysis used in this research approach will be explored.